Is Reduced Strontium Titanate a Semiconductor or a Metal? - Christian Rodenbücher; Christo Guguschev; Carsten Korte; Sebastian Bette; Kristof Szot (Crystals, 2021)
In recent decades, the behavior of SrTiO3 upon annealing in reducing conditions has been under intense academic scrutiny. Classically, its conductivity can be described using point defect chemistry and predicting n-type or p-type semiconducting behavior depending on oxygen activity. In contrast, many examples of metallic behavior induced by thermal reduction have recently appeared in the literature, challenging this established understanding. In this study, we aim to resolve this contradiction by demonstrating that an initially insulating, as-received SrTiO3 single crystal can indeed be reduced to a metallic state, and is even stable against room temperature reoxidation. However, once the sample has been oxidized at a high temperature, subsequent reduction can no longer be used to induce metallic behavior, but semiconducting behavior in agreement with the predictions of point defect chemistry is observed. Our results indicate that the dislocation-rich surface layer plays a decisive role and that its local chemical composition can be changed depending on annealing conditions. This reveals that the prediction of the macroscopic electronic properties of SrTiO3 is a highly complex task, and not only the current temperature and oxygen activity but also the redox history play an important role.